2018
DOI: 10.1097/jte.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Perception Versus Reality: Estimated and Actual Online Content Consumption Comparisons and Relationships to Classroom Performance

Abstract: Introduction. As students and faculty are increasingly becoming more comfortable with technology, physical therapy programs are using the flipped classroom (FC) to provide an environment more conducive to active and problem-based learning. Most literature on students in graduate level health care professional programs rely on subjective student report. To our knowledge, no studies have compared objective actual student consumption of online content to subjective student perception of online content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although students have generally responded positively to this educational approach, it has been reported that this method should not be used for all classes and that some skills are harder to retain through online consumption. 5 Murray et al 3 compared outcomes on written examination questions between physical therapist students who received traditional instruction with those who participated in a flipped classroom online model. The authors reported that there were no significant differences in student outcomes between the instructional models, suggesting that hybrid models of instruction can allow educators to use class time more efficiently while producing similar outcomes in student learning and performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although students have generally responded positively to this educational approach, it has been reported that this method should not be used for all classes and that some skills are harder to retain through online consumption. 5 Murray et al 3 compared outcomes on written examination questions between physical therapist students who received traditional instruction with those who participated in a flipped classroom online model. The authors reported that there were no significant differences in student outcomes between the instructional models, suggesting that hybrid models of instruction can allow educators to use class time more efficiently while producing similar outcomes in student learning and performance.…”
Section: Review Of Literaturementioning
confidence: 99%